Enzymatic oxidation of volatile malodorous organosulfur compounds in a two-phase reactor - Cruz, Julio C.; García, Jesús; Ayala, Marcela (TIP Revista Especializada en Ciencias Químico-Biológicas, 2015)
In this work we report the oxidation of volatile organosulfur compounds (VOC) catalyzed by the enzyme chloroperoxidase from Caldariomyces fumago. VOC are regarded as atmospheric pollutants due to their unpleasant odor and low detection threshold. Diethyl sulfide, dimethyl disulfide, propanethiol, butanethiol and hexanethiol were found to be substrates for the enzyme in a liquid medium reaction at pH 6, under peroxidatic conditions. Product analysis showed that sulfides were oxidized to their respective sulfoxides whereas thiols were oxidized to the corresponding disulfides. The identified products showed significantly lower vapor pressure than the parental compounds; thus, the products are not considered atmospheric pollutants. A 70-mL two-phase reactor was assembled in order to determine the efficiency of the enzymatic treatment. The liquid phase, consisting of 15% organic solvent and 85% buffer, was contacted with the gaseous phase, consisting of a substrate-enriched air stream. Using dimethyl disulfide as model substrate, we found that only enzymatic oxidation occurred in this system; by controlling the enzyme and peroxide concentration, we found that the substrate is transferred to the aqueous phase where 1 mol of enzyme converted approximately 12,400 mol of substrate, thus highlighting the potential of enzymatic treatment of malodorous gaseous streams.